THE LEGAL POSITION OF THE DIRJEN BINAWAS JAMSOSTEK POST-SOCIAL SECURITY DECREE NO. 27/PUU-IX/2011 OF ARTICLE 59-66 ACT NO. 13 the YEAR 2003 ON EMPLOYMENT - Mahmud Mahmud (International Peneliti Ekonomi, Sosial dan Teknologi, 2019)
The purpose of this research is to determine the implementation of the post-impact Constitutional Court verdict No. 27/PUU-IX/2011, on the Outsourcing Labor regulation (power-over) in Indonesia. The study uses a normative juridical method of approach, by examining the library material or secondary data, named normative legal research or literature law research (in addition to research on sociological or empirical law which mainly examines primary data. The research results show that with the publication of circular letter number B. 31/PHIJSK/I/2012 The post of Constitutional Court ruling is irrelevant because the circular letter is not included Legislation. With the issuance of the circular letter is a legal action of the Government with the intention that there is no confusion in implementing the rules on outsourcing the post-Constitutional Court ruling and its supervision is implemented by the agency responsible for the field of employment